Knowledge about food additives among adults – pilot study: Knowledge about food additives among adults - Avram, Laura; Avram, Calin; Olah, Peter; Rus, Victoria; Georgescu, Ion Mihai; Bucur, Oana maria; Florina, Ruta (Progress in Nutrition, 2021)
Introduction. To gain as more benefits as possible from food labels, the level of knowledge of consumers in Romania about the information on the food labels needs to be assessed.Aim. The study aims to provide practical results and orientations based on consumers’ perspectives, not only for food processors, retailers, but also for designing efficient labels so that for the purchase of food and semi-prepared products they allow the choice of discerning products that meet the requirements buyer such as: caloric content, sugar, allergens, additives.Methods. To complete this pilot, cross-sectional study, an on-line evaluation questionnaire was developed and disseminated between December 2016 and February 2017.Results. Of the total of 476 people surveyed, 96 of them are men (namely 20.16%) and the rest are women (namely 79.84%). Of those surveyed 214 (namely 45%) of them go shopping at least 3 times a week, those in the rural area have only 36% (namely 32 people). Most 348 people (73%) shop in the supermarket or hypermarket. Residency plays an important role in the knowledge of food additives, people in the rural area have less knowledge than those from the urban area with regard to the meaning of "E" on the packaging (OR = 3.13, 95% CI: 1.86-5.26), do not know that food additives are not harmful (OR = 0.58, 95% CI: 0.36-0.94), as well as about adequate knowledge of food additives(OR=3.46, 95 % CI: 2.01-5.95).Conclusions. An information on the significance of food additives would be beneficial to both the population and  the country. This would allow the choice of foods that correspond to the health of the buyer. Awareness and information of the population of the potential elimination or addition of food additives and their function in the final product.